Melatonin influences methyl jasmonate-induced protection of photosynthetic activity in wheat plants against heat stress by regulating ethylene-synthesis genes and antioxidant metabolism - Zebus Sehar; Mehar Fatma; Sheen Khan; Iqbal R. Mir; Gholamreza Abdi; Nafees A. Khan (Scientific Reports, 2023)
Abstract Melatonin (MT) and methyl jasmonate (MeJA) play important roles in the adaptation of plants to different stress factors by modulating stress tolerance mechanisms. The present study reports the involvement of MT (100 µM) in MeJA (10 µM)-induced photosynthetic performance and heat stress acclimation through regulation of the antioxidant metabolism and ethylene production in wheat (Triticum aestivum L.) plants. Plants exposed to 40 °C for 6 h per day for 15 days and allowed to retrieve at 28 °C showed enhanced oxidative stress and antioxidant metabolism, increased 1-aminocyclopropane-1-carboxylic acid (ACC) synthase (ACS) activity and ethylene production, and decreased photosynthetic performance. In contrast, the exogenously applied MT and MeJA reduced oxidative stress through improved S-assimilation (+ 73.6% S content), antioxidant defense system (+ 70.9% SOD, + 115.8% APX and + 104.2% GR, and + 49.5% GSH), optimized ethylene level to 58.4% resulting in improved photosynthesis by 75%. The use of p-chlorophenyl alanine, a MT biosynthesis inhibitor along with MeJA in the presence of heat stress reduced the photosynthetic performance, ATP-S activity and GSH content, substantiated the requirement of MT in the MeJA-induced photosynthetic response of plants under heat stress. These findings suggest that MeJA evoked the plant’s ability to withstand heat stress by regulating the S-assimilation, antioxidant defense system, and ethylene production, and improving photosynthetic performance was dependent on MT.